2010
DOI: 10.1021/jo101027h
|View full text |Cite
|
Sign up to set email alerts
|

Direct B-Alkyl Suzuki−Miyaura Cross-Coupling of 2-Halopurines. Practical Synthesis of ST1535, a Potent Adenosine A2A Receptor Antagonist

Abstract: The scope and limitations of using palladium-catalyzed cross-coupling reactions of diverse butyl metal species with two different 2-halopurines were evaluated. While tributylboranes reacted readily and regioselectively with both 2-chloro-6-dibenzylaminopurines and 2-iodo-6-chloropurines, all the other alkyl metal species were much less reactive and gave very poor yield and/or selectivity of the desired product. This protocol was applied to the synthesis of an important adenosine A(2A) receptor antagonist, ST15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…264 The alkylation of these particular substrates was challenging but highly desirable, as it offers a concise route for the synthesis of ST1535, a potent adenosine A 2A receptor antagonist. Fortunately, applying a B -alkyl Suzuki-Miyaura cross-coupling in the presence of Cs 2 CO 3 and catalytic Pd (dppf)Cl 2 in THF afforded 2-alkylated purines in high yields.…”
Section: Cross-coupling With Alkylboron Reagentsmentioning
confidence: 99%
“…264 The alkylation of these particular substrates was challenging but highly desirable, as it offers a concise route for the synthesis of ST1535, a potent adenosine A 2A receptor antagonist. Fortunately, applying a B -alkyl Suzuki-Miyaura cross-coupling in the presence of Cs 2 CO 3 and catalytic Pd (dppf)Cl 2 in THF afforded 2-alkylated purines in high yields.…”
Section: Cross-coupling With Alkylboron Reagentsmentioning
confidence: 99%
“…Regioisomers were separated by flash chromatography on silica gel. [24,25] Scheme 10. Synthesis of compounds 45a-f in S N Ar reactions with azoles.…”
Section: C(8)-linked Azolylpurine Derivativesmentioning
confidence: 99%
“…[25] One can conclude that halopurines, inosine-and guanosine-derived sulfonate esters, and compounds possessing phosphorus-containing or O 6 -(benzotriazol-1-yl) leaving groups are suitable for the incorporation of azolyl groups in the purine system. The obtained 1,2,4-and 1,2,3-triazolylpurine derivatives can be used in further S N Ar reactions with other nucleophiles.…”
Section: C(8)-linked Azolylpurine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, during a study on the synthesis of ST1535, a potent adenosine A 2A receptor anatgonist, Bartoccini et al 185. found that 2‐ n ‐butyl‐ ( 505a ) and 2‐ethyl‐6‐chloro‐9‐methyl‐9 H ‐purines ( 505b ) could be efficiently and selectively synthesized by the PdCl 2 (dppf)‐catalyzed reaction of 6‐chloro‐2‐iodo‐9‐methylpurine ( 503 ) with 2.0 equiv.…”
Section: Cross‐coupling Reactions Of Polyhalogenated Heterocycle‐anmentioning
confidence: 99%